To 110th Anniversary of the Federal Public Health Institution Astrakhan Plague Control Station - V. V. Kabin; B. L. Agapov; A. A. Kuznetsov; A. N. Matrosov (Проблемы особо опасных инфекций, 2011)
Presented is a historical essay on the work of one of the oldest Russian anti-plague institutions - Astrakhan Plague Control Station. Noted is the fact that specialists of this institution made a substantial contribution to the development of the theory of plague natural focality and other contagious infections, as well as to the provision for and implementation of measures for epidemiological surveillance and prophylaxis of plague and other particularly dangerous infectious diseases in the territory of the North-West Caspian sea region.